PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 038 BALAM SEMPURNA KECAMATAN BAGAN SINEMBAH - Cristina S, Agus Dian; Kurniaman, Otang; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research has a purpose to increase the result of students’ mathematic lesson in fourth grade of SD Negeri 038 Balam Sempurna Kecamatan Bagan Sinembah. This research had done in March until April 2015. This subject of the research are the students in fourth grade of SD Negeri 038 Balam Sempurna Kecamatan Bagan Sinembah which are 28 person. The result of students’ mathematic lesson is low because of the teacher is never give the contextual problem to the students and the teacher is never allow the students finished the contextual problem in their days of life. The formulation of problem research is: is the implementation of mathematic realistic on Indonesia can increase the result of students’ mathematic lesson in fourth grade of SD Negeri 038 Balam Sempurna Kecamatan Bagan Sinembah. This thesis presented the increasing of the students’ test result with the implementation of mathematic realistic on Indonesia. This research consist of two cycles with research’s instruments are learning instruction ( silabus, RPP, LKS, test), observation sheet of teacher and student. The result of the students’test indicated the increasing from the first score at the first cycle which has the average 65,07 become 79,11 at the end of first cycle and rose again at the end of second cycle which has the average 83,04. So that, the increasing of the test result from the first score to the first cycle is 14,04 point which is the precentage of increasing is 21,58%, whereas from the first cycle to the second cycle is 3,93 point which is the precentage of increasing is 27,62 %. The result of the analysis of the students activities’ data at the first cycle in first meeting is 54,16% and at the second meeting get increasing become 66,67%. At the second cycle in first meeting is 83,33% get increasing become 95,83% in second meeting. Whereas the teacher activities’ data at the first cycle in first meeting is 58,33% get increasing in second meeting become 83,33%. At the second cycle in first meeting is 86,11% get increasing in second meeting become 91,67%. So that, the implementation of mathematic realistic on Indonesia can increase the result of students’ mathematic lesson in fourth grade of SD Negeri 038 Balam Sempurna Kecamatan Bagan Sinembah.Key Word : Implementation of Mathematic Realistic On Indonesia, The Result of Mathematic Lesson.